MIGA Annual Report 2009 - Multilateral Investment Guarantee Agency (Washington, DC: World Bank, 2012)
For Multilateral Investment Guarantee Agency (MIGA), the challenge this year has been promoting foreign direct investment (FDI) into developing countries at a time when investment flows are slumping. While many investors shied away from projects because of the difficult investment climate, those who have been doing business recognized the need for the kind of political risk guarantees MIGA provides. This year, MIGA provided $1.4 billion in guarantees for a range of projects, down from the agency's banner year of $2.1 billion in guarantees in 2008. But MIGA also experienced far fewer cancellations of existing coverage this year than in previous years. MIGA is also supporting projects to help the most vulnerable. This year, the agency entered into an innovative contract to facilitate up to $100 million of investments to small and medium-size enterprises in Sub-Saharan Africa, businesses which account for most of the continent's jobs. MIGA has also focused on internal changes. At a time of financial crisis, promoting FDI depends on moving quickly to meet the emerging needs of clients. This will enhance MIGA's operational flexibility and procedural efficiency, and should lead to more business while strengthening MIGA's position as a self-standing enterprise.